Fabrication of quantum dots for biomedical applications - Tan, Li Choong. (2013)
This study utilised a bottom-up direct aqueous-phase synthesis technique to synthesize high quality Cadmium-Tellurium (CdTe) Quantum Dots capped with Mercaptopropionic acid (MPA). Direct aqueous-phase synthesis is a two-step technique which involves the preparation of the Cd and Te precursors and the subsequent synthesis of CdTe QDs. The QDs were refluxed at different timing during synthesis and the fluorescence and absorption spectrum of QDs were measured to study the characteristic of CdTe QDs growth. The influences of the precursor Cd:Te molar ratio and surfactant to precursor MPA:Cd molar ratio on the quality of the CdTe QDs synthesized was investigated. Centrifugation technique was used to separate CdTe QDs of different sizes. Bio-imaging of pancreatic cancer cells using CdTe QDs synthesized were performed to demonstrate the use of QDs for biomedical applications.